PENGARUH KURS, INFLASI, DAN SUKU BUNGA TERHADAP HARGA SAHAM PADA PERUSAHAAN YANG GO PUBLIC DI BURSA EFEK INDONESIA - Diyah Ratnasari; Abdul Wahid Mahsuni; M. Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2019)
ABSTRACTThe reason for choosing a research topic for companies that go public on the Indonesia Stock Exchange is based on whether exchange rates, inflation and interest rates affect stock prices. Because this research is expected to be used by potential investors in making investment decisions. The purpose of this study is to find out how the influence of exchange rates, inflation and interest rates simultaneously and partially on stock prices in companies that go public on the Indonesia Stock Exchange. Population members are companies that are listed on the Indonesia Stock Exchange and their shares are traded during the period of 2016 to 2018, namely as many as 555 companies. Sampling of this study uses proportional random sampling, which is as many as 20 companies for 3 years, so there are 60 company data. Based on the results of the study obtained R square (R2) = 0.714. This shows that at 71.4% the changes that occur in the stock price are explained by exchange rates, inflation and interest rates and the remaining 28.6% is explained by other variables not examined or not included in the model. Based on discussion and analysis of data, it can be seen that Exchange Rate, Inflation and Interest Rate have a simlan and partial effect on stock prices in companies that go public on the Indonesia Stock Exchange. Keywords: Exchange Rate, Inflation, Interest Rate, Stock Price